Self-Assessment of Well-Being as an Indicator of Quality of Life of Former War Prisoners : A Croatian Study - Lončar, Mladen (Array, 2011)
The impact of war on the population is vast, especially when it comes to those who were directly affected by war, among other things as concentration camp detainees. Because of the specific war experience of this population it is important to better understand the possible contribution of key socio-demographic variables, war traumatization and acute disturbances in mental health to their subjective assessment of their own well-being, which represents a psychological category and is based on a subjective assessment. The starting point is a theoretical precept according to which individual characteristics, together with war experience, can have repercussions on mental health, and eventually on the general well-being of an individual and their quality of life. The study comprised 184 participants who had given their informed consent for participation and filled out complete questionnaires. The participants were a convenience sample of male persons who had survived war captivity in the Homeland War in the period from 1991 to 1995. The study was conducted as part of the physical examinations at the University Hospital »Fran Mihaljevi}; ; ; ; ; ; « in Zagreb. The data was collected using several self-evaluation measuring instruments one of which served to collect socio-demographic data, two to collect data on the participants’ mental health, one for the data on the participants’ combat and war experiences and one to assess the participants’ well-being. The data obtained suggest that only avoidance and arousal symptoms and psychosomatic difficulties are predictors of the well-being of persons who have experienced war captivity.